Animal models for analysis of hypersensitivity reactions to Shuanghuanglian injection. (June 2020) - Xiao, Peng; Hou, Li; Liu, Zhaohua; Mu, Yanling; Liu, Zengxiang; Wang, Jiao; Qiu, Shidong
Highlights: SHLI induces anaphylactoid reactions in mouse, rat and dog models. SHLI could activate the complement system in dogs and rats. SHLI could produce an increase in vascular permeability. We demonstrate a means for establishing an evaluation system of anaphylactoid reactions. Abstract: Among a variety of traditional Chinese medicines, Shuanghuanglian injection (SHLI), has the highest incidence of injection-induced immediate hypersensitivity reactions (IHRs). However, the precise mechanisms of SHLI-induced IHRs remain to be understood. In the present study, we characteriszed IHRs as induced by SHLI by recording changes in physiological and hemodynamic indicators following intravenous injections of SHLI in rats and dogs. The results indicate that SHLI induced the release of histamine, decreased mean arterial blood pressure (MAP), increased SC5b-9 in rats and dogs, increased C4d and Bb in dogs without any changes in IgE. n vitro incubation of SHLI with serum from dogs in the presence of an inhibitor of complement activation (EGTA/Mg 2+ ) resulted in an increase in C4d. These results suggest that SHLI induces anaphylactoid reactions in rats and dogs. Furthermore, SHLI appears to activate the complement system through classical and alternative pathways in dogs in vivo . Additional experiments in mice demonstrated that SHLI induces locus coeruleus infiltration and results in significant increase in vascular permeability within the skin of mice. We established a reliable method for the evaluation of anaphylactoid reactions induced by complex compounds, using multiple physiological indicators, different experimental models in vivo and in vitro .